2014
DOI: 10.1101/lm.032037.113
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic nucleotide–gated channels, calmodulin, adenylyl cyclase, and calcium/calmodulin-dependent protein kinase II are required for late, but not early, long-term memory formation in the honeybee

Abstract: Memory is a dynamic process that allows encoding, storage, and retrieval of information acquired through individual experience. In the honeybee Apis mellifera, olfactory conditioning of the proboscis extension response (PER) has shown that besides short-term memory (STM) and mid-term memory (MTM), two phases of long-term memory (LTM) are formed upon multiple-trial conditioning: an early phase (e-LTM) which depends on translation from already available mRNA, and a late phase (l-LTM) which requires de novo trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 84 publications
4
52
0
Order By: Relevance
“…We showed that the MER to an odor is increased by pairing of the odor with water US. This is analogous to olfactory conditioning of proboscis extension responses (PERs) in honey bees, in which pairing of an odor and sucrose US leads to an increase of the PER (Menzel & Giurfa, 2006;Matsumoto, Sandoz, Devaud, Lormant, Mizunami, & Giurfa, 2014). We also showed that the MER to an odor is decreased by pairing of the odor with sodium chloride US, thus allowing study of appetitive conditioning and aversive conditioning in a similar experimental situation.…”
Section: Experimental Procedures To Study Learning and Memory In Cricsupporting
confidence: 57%
“…We showed that the MER to an odor is increased by pairing of the odor with water US. This is analogous to olfactory conditioning of proboscis extension responses (PERs) in honey bees, in which pairing of an odor and sucrose US leads to an increase of the PER (Menzel & Giurfa, 2006;Matsumoto, Sandoz, Devaud, Lormant, Mizunami, & Giurfa, 2014). We also showed that the MER to an odor is decreased by pairing of the odor with sodium chloride US, thus allowing study of appetitive conditioning and aversive conditioning in a similar experimental situation.…”
Section: Experimental Procedures To Study Learning and Memory In Cricsupporting
confidence: 57%
“…In the honey bee, seven ACs have been identified, with transmembrane AmAC8 likely belonging to the Ca 2+ -CaM activated enzyme family (Balfanz et al, 2012). Matsumoto et al (2014) injected pharmacological inhibitors of AC directly into the brain of honey bees and observed impairment of long-term memory. Such studies with inhibitors provide evidence of the essentiality of proper AC signaling.…”
Section: Creb Signaling Pathways and Memorymentioning
confidence: 99%
“…Whereas earlier attempts to unravel molecular and biochemical pathways associated with learning and memory in the honeybee were often based on pharmacological tools (e.g. Felsenberg et al, 2011;Müller, 1996Müller, , 2000, in recent years manipulations using genetic tools such as RNA interference (RNAi) became more accessible (El Hassani et al, 2012;Farooqui et al, 2003;Louis et al, 2012;Matsumoto et al, 2014;Müssig et al, 2010). The possibilities for a combination of several manipulative approaches and the availability of robust associative learning assays make the honeybee an excellent model organism to study the link between behavioral plasticity and its molecular basis.…”
Section: Introductionmentioning
confidence: 99%